2023
DOI: 10.3389/fped.2022.1019825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of presepsin as a diagnostic tool in newborns with risk of early-onset neonatal sepsis

Abstract: ObjectivesTo evaluate the efficacy of presepsin (P-SEP) as a potential biomarker of early-onset neonatal sepsis (EOS) and compare it to other routinely used markers of inflammation. To establish the cut-off values of P-SEP for EOS.Study design184 newborns were prospectively recruited between January 2018 to December 2020. Newborns >34th gestational week with suspected infection were included up to 72 h after delivery, and divided into three categories (i.e., unlikely, possible, and probable infection) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…However, differences in presepsin concentrations between EOS and LOS cases and differences in reference ranges with increasing postnatal age underline the importance of studying them as separate entities [ 9 , 14 ]. To the best of our knowledge, only six previous studies reported diagnostic accuracy measures of presepsin specifically for EOS [ 13 , 19 , 20 , 21 , 22 , 23 ]. Five of these studies included only term-born infants [ 20 , 22 ] or mainly term-born infants [ 19 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, differences in presepsin concentrations between EOS and LOS cases and differences in reference ranges with increasing postnatal age underline the importance of studying them as separate entities [ 9 , 14 ]. To the best of our knowledge, only six previous studies reported diagnostic accuracy measures of presepsin specifically for EOS [ 13 , 19 , 20 , 21 , 22 , 23 ]. Five of these studies included only term-born infants [ 20 , 22 ] or mainly term-born infants [ 19 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only six previous studies reported diagnostic accuracy measures of presepsin specifically for EOS [ 13 , 19 , 20 , 21 , 22 , 23 ]. Five of these studies included only term-born infants [ 20 , 22 ] or mainly term-born infants [ 19 , 21 , 23 ]. Three of these studies compared presepsin concentrations between clinical EOS cases and healthy controls without a suspicion of infection and reported AUC values of 0.77, 0.95 and 0.97, respectively [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent evaluation has shown that the diagnostic efficacy of P-SEP was highest when used in combination with IL-6 and CRP compared when the biomarker was used alone. The area under the Rock curve (AUC) for discriminating the probable infection group from the unlikely infection group was 0.97 (95% CI: 0.911–0.990) vs. 0.845 (95% CI: 0.708–0.921) [ 202 ].…”
Section: Biomarkers Presently Used In Clinical Practicementioning
confidence: 99%
“…In neonates, two studies evaluated cutoff levels for diagnosing neonatal sepsis: the first established a cutoff value of 485 pg/mL, with 97.8% sensitivity and 94.1% specificity [11], and the second established a cutoff value of 538 ng/mL, with 79.5% sensitivity and 87.2% specificity [12]. Furthermore, in a recent study by Pospíšilová et al [13], P-SEP was evaluated as a potentially effective diagnostic tool for assessing the risk of early-onset neonatal sepsis in newborns.…”
Section: Introductionmentioning
confidence: 99%